Ibuprofen and acute kidney injury in the newborn - Fanos, Vassilios; Antonucci, Roberto; Zaffanello, Marco (The Turkish Journal of Pediatrics, 2010)
The pharmacological treatment of patent ductus arteriosus (PDA) in preterm infants remains a controversial issue, particularly with regard to the type of drug to be prescribed (ibuprofen or indomethacin) and the timing of the treatment, given their comparable effectiveness. For many years, indomethacin has been the drug of choice in the treatment of PDA. In April 2006, the United States Food and Drug Administration approved the use of ibuprofen lysine for closure of clinically significant PDA in premature infants < 32 weeks' gestation and weighing 500-1500 g. The available knowledge on the effects of ibuprofen on renal function in the neonate is discussed herein, since the good renal tolerability of this drug is a major argument in favor of its use in the routine treatment of PDA.